Types and Density of Gastropods in Mangrove Ecosystem in Kampung Madong Tanjungpinang Kepulauan Riau - Asri Mentari Nasution; Adriman Adriman; Nur El fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study aims to determine the type and abundance of gastropods in the mangrove ecosystem in Madong Village. This research was conducted in July 2019 which is located in Kampung Madong Tanjungpinang Kepulauan Riau. Gastropod sampling using the line transects method. At the research location, there were 3 stations and each station consisted of 3 quadrants measuring 1x1 m. The results of the study found 13 species of gastropods. The abundance of gastropod ranged from 41,111 – 150,000 organism/ha, diversity index values (H ') ranged from 0.699 – 3.454, dominance index (C) values ranged between 0.096 – 0.693 and uniformity index values ranged from 0.699 – 0.963. Differences in the value of density, diversity, dominance, and uniformity at each station caused by differences in mangrove conditions, substrates and activities community.Keywords: Gastropod Density, Mangrove Ecosystem, Substrate, Kampung Madong